Politics of participation in Integrated Watershed Development Programmes in Bundelkhand, India: Insights from a gender and social inclusion perspective - Ravula, Padmaja; Chakraborty, Ananya; Kasala, Kavitha (International Crops Research Institute for the Semi-Arid Tropics, 2023)
The Integrated Watershed Development Programme (IWDP) is key for rejuvenation and improvement of waterscarce landscapes in India. Despite policy guidelines, there has been limited success in ensuring community participation and inclusion in IWDPs, especially for women and people from vulnerable social groups. This study attempted to explore the politics of inclusion and exclusion because local hierarchies of caste and gender inhibit decision-making, access to services, participation and benefits from IWDPs. Mixed methods, comprising of sex-disaggregated information from a survey of 222 households combined with qualitative and participatory tools, were used to understand the barriers and enabling conditions for inclusion in the IWDP. The main findings indicate that men from the larger landowning community were more likely to participate in the villagelevel watershed committee (WSC) and benefit from the program compared to others. The practical needs of women—based on their gender roles such as fetching water, grazing small ruminants, and collecting firewood for cooking—still continue to be valid in these locations, and these roles were overlooked when designing some interventions. The project did not acknowledge or address gender barriers that inhibit women from participating in WSCs, such as lower levels of literacy, gender norms around mobility and interaction of women, and knowledge of skills like driving vehicles. We argue that building sustainable watershed structures need to hinge on the dual pillars of inclusive participation, and equitable distribution and local governance of program outcomes. Issues of gender and social inclusion need to be integrated within the planning and design phases rather than treating them as supplementary concerns.